The Influence of Competence and Self-Efficacy on the Professionalism of Widyaiswara with Work Motivation as a Mediating Variable (Case Study at the Jakarta Religious Education and Training Center): - Dedi Hendra Lesmana Harahap; Tajuddin Pogo (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to analyze the effect of competence and self-efficacy on the professionalism of widyaiswara at the Jakarta Religious Education and Training Center, with work motivation as a mediating variable. The population of this study was made up of alumni of training participants in the 2022 working area at BDK Jakarta, with a sample size of 110 people. The data analysis method uses the SEM-PLS technique. The results of this study found empirical evidence that partially competence and self-efficacy have a positive effect on Widyaiswara work motivation. Competence, self-efficacy, and work motivation partially also have a positive effect on the professionalism of Widyaiswara Widyaiswara BDK Jakarta. Competence affects the professionalism of Widyaiswara through work motivation. Self-efficacy also affects the professionalism of Widyaiswara through work motivation.